The efficacy of sodium glucose co-transport-2 inhibitors on glycemic control for patients with type 1 diabetes mellitus: A protocol for systematic review and meta-analysis. Issue 27 (9th July 2021) - Zhang, Yajie; Gan, Ping; Huo, Yanan
Abstract: Background: Currently, there are a number of sodium glucose co-transport-2 (SGLT2) inhibitors that are under development or in clinical trials. Prior meta-analyses had established the safety and efficacy of SGLT2 inhibitors in type 1 diabetes mellitus (T1DM), but with low level of evidences and inconsistent conclusions. However, recently many new randomized clinical trials (RCTs) have been published, we hence try to design a study protocol to assess the effect of SGLT2 inhibitors on cardiovascular events via a comprehensive meta-analysis of data from much more RCTs, including sensitivity and subgroup analyses. Methods: We will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guidelines to conduct this meta-analysis. Two investigators will perform a systematic search of scientific literature in the databases (from conception through June 12, 2021), including PubMed, Embase, and Cochrane Central Register of Controlled Trials. This meta-analysis will be conducted using RevMan statistical software. The risk of bias for each included study will be assessed using the Cochrane Risk of Bias Assessment Tool. Results: Our protocol is conceived to test the hypothesis that SGLT2 inhibitors could lead to better outcomes in patients presenting with T1DM. Registration number: 10.17605/OSF.IO/ZD8WX.